Characterizing the eddy field in the Arctic Ocean halocline. Issue 12 (22nd December 2014) - Zhao, Mengnan; Timmermans, Mary‐Louise; Cole, Sylvia; Krishfield, Richard; Proshutinsky, Andrey; Toole, John
Abstract Ice‐Tethered Profilers (ITP), deployed in the Arctic Ocean between 2004 and 2013, have provided detailed temperature and salinity measurements of an assortment of halocline eddies. A total of 127 mesoscale eddies have been detected, 95% of which were anticyclones, the majority of which had anomalously cold cores. These cold‐core anticyclonic eddies were observed in the Beaufort Gyre region (Canadian water eddies) and the vicinity of the Transpolar Drift Stream (Eurasian water eddies). An Arctic‐wide calculation of the first baroclinic Rossby deformation radius Rd has been made using ITP data coupled with climatology; Rd ∼ 13 km in the Canadian water and ∼8 km in the Eurasian water. The observed eddies are found to have scales comparable to Rd. Halocline eddies are in cyclogeostrophic balance and can be described by a Rankine vortex with maximum azimuthal speeds between 0.05 and 0.4 m/s. The relationship between radius and thickness for the eddies is consistent with adjustment to the ambient stratification. Eddies may be divided into four groups, each characterized by distinct core depths and core temperature and salinity properties, suggesting multiple source regions and enabling speculation of varying formation mechanisms.